2016
DOI: 10.1371/journal.pone.0164449
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans ISW2 Regulates Chlamydospore Suspensor Cell Formation and Virulence In Vivo in a Mouse Model of Disseminated Candidiasis

Abstract: Formation of chlamydospores by Candida albicans was an established medical diagnostic test to confirm candidiasis before the molecular era. However, the functional role and pathological relevance of this in vitro morphological transition to pathogenesis in vivo remain unclear. We compared the physical properties of in vitro-induced chlamydospores with those of large C. albicans cells purified by density gradient centrifugation from Candida-infected mouse kidneys. The morphological and physical properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…Nos3 -/- mice had significantly lower kidney neutrophil infiltration compared with infected WT kidneys. Kidney is the major target organ in disseminated candidiasis and is responsible for mouse mortality as shown previously [24,35,36,43,47,54,55]. The decreased recruitment of innate immune cells was associated with a decreased fungal burden at the sub-acute phase in the infected Nos3 -/- kidneys.…”
Section: Discussionsupporting
confidence: 55%
“…Nos3 -/- mice had significantly lower kidney neutrophil infiltration compared with infected WT kidneys. Kidney is the major target organ in disseminated candidiasis and is responsible for mouse mortality as shown previously [24,35,36,43,47,54,55]. The decreased recruitment of innate immune cells was associated with a decreased fungal burden at the sub-acute phase in the infected Nos3 -/- kidneys.…”
Section: Discussionsupporting
confidence: 55%
“…The biological function of chlamydospores is unknown and the reasons why only C. albicans , and its closely related species C. dubliniensis , have retained this phenotype throughout evolution remains a mystery ( Palige et al 2013 ; Navarathna et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that chlamydospores could allow the survival of the fungus in harsh environmental conditions or, given that C. albicans and C. dubliniensis are restricted to humans, could facilitate persistence or survival of these species within the mammalian host ( Staib and Morschhäuser 2007 ). However, rarely have chlamydospores been observed in infected tissues ( Heineman et al 1961 ; Ho and O'Day 1981 ; Chabasse et al 1988 ; Cole et al 1991 ) although a recent study documenting their formation in the kidneys of experimentally infected mice suggested a role in pathogenesis ( Navarathna et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the human pathogenic yeast Candida albicans , several genes were found to be involved in chlamydospore formation, including homeobox transcription factor (TF) gene grf10 (Ghosh et al, 2015), phosphate mannose synthase encoding genes (Juchimiuk et al, 2015), mitogen-activated protein kinase gene hog1 (Eisman et al, 2006), gene encoding dolichol phosphate mannose synthase (Juchimiuk et al, 2015), chromatin remodeling complex gene isw2 (Nobile et al, 2003; Navarathna et al, 2016), MDS3, RIM101, RIM13, SCH9 , and SUV3 (Nobile et al, 2003). Meanwhile, very few genes in filamentous fungi were found relative to chlamydospore formation, the limited examples include VELVET gene vel1 in biocontrol fungus Trichoderma virens (Mukherjee and Kenerley, 2010); and a group of genes in Clonostachys rosea identified from a study using RNA-seq (Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%